Slovak Republic : Financial System Stability Assessment, including Reports on the Observance of Standards and Codes on the following topics; Monetary and Financial Policy Transparency, Banking Supervision, Securities Regulation, Insurance Regulation, Corporate Governance, Payment Systems; and Summary Assessments of Insolvency and Credit Rights Systems and Anti-Money Laundering Practices. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2002)
This paper presents key findings of the Financial System Stability Assessment for the Slovak Republic, including Reports on the Observance of Standards and Codes on Monetary and Financial Policy Transparency, and Banking Supervision. Successful stabilization and an ambitious structural reform program since 1998 and the rehabilitation and privatization of the public banks in the Slovak Republic have produced a banking and financial sector that appears to be robust to a range of macroeconomic or financial sector shocks. Banking supervision is weak, but the National Bank of Slovakia has launched a medium-term program to strengthen it.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet